[PP.09.04] PATTERNS OF RENAL AND CARDIAC HAEMODYNAMICS IN SYMPTOMATIC ESSENTIAL HYPERTENSIVES. (September 2016) - Kintis, K.; Tsioufis, C.; Dimitriadis, K.; Konstantinidis, D.; Kalos, T.; Kasiakogias, A.; Nikolakopoulos, I.; Bazoukis, G.; Patsilinakos, S.; Tousoulis, D.
Abstract : Objective: It is noteworthy that asymptomatic organ damage (OD) is a determinant of overall cardiovascular (CV) risk in hypertension and also the risk increases as the number of damaged organs increases. We estimated whether increased renal haemodynamics in conjunction with pronounced left ventricular (LV) filling pressure were accompanied by target OD in hypertension. Design and method: We studied 360 patients with essential hypertension [183 males, aged 55 years, office blood pressure (BP) = 144/86 mmHg] that underwent transthoracic echocardiographic study for determination of mitral annular early diastolic velocity (E/e') and blood sampling for assessment of metabolic profile. Moreover, data on renal resistive index (RRI), obtained by Doppler ultrasound sampling of the intrarenal arteries, were retrospectively analyzed. The distributions of RRI and E/e' were split by the median (0.623 and 7.8, respectively). Results: Age, systolic and diastolic office BP, body mass index (BMI) and E/e' were the independent predictors of RRI (R2 = 0.478, p < 0.001). Age, systolic office BP, and RRI were the independent predictors of E/e' (R2 = 0.400, p < 0.001). Patients with high RRI and high E/e' (n = 122), compared to those with low RRI and low E/e' (n = 78) were characterized by increased LVMIheight (by 6.2 g/m2.7, p < 0.05), office PP (by 16.4, p < 0.001), ACR (by 25.1 mg/g, p < 0.001), PWV (by 1.6 m/s, p < 0.05), and prevalence of LVH (45 vs. 12 %, p < 0.001). Conclusions: Increased RRI in conjunction with pronounced left ventricular filling pressure is accompanied by augmented LV mass, PP, ACR, PWV, and higher LVH rates. Furthermore, the coexistence of impaired renal and cardiac haemodynamics suggests the occurrence of multiple target OD progression.